1968
DOI: 10.1111/j.1365-2621.1968.tb03655.x
|View full text |Cite
|
Sign up to set email alerts
|

Arbutin and a Related Glucoside in Immature Pear Fruit

Abstract: SUMMARY– Arbutin (p‐hydroxyphenyl‐β‐D‐glucoside) was separated from other phenols in an extract of immature fruit of Pyrus C.V. Kieffer by preparative paper chromatography and isolated as the penta‐acetyl derivative. A monoacetylarbutin (p‐hydroxyphenyl‐6‐0‐acetyl‐β‐D‐glucoside) was identified in the same pear extract. In addition, arbutin was found in both mature and immature pears, but at much higher levels in the immature fruit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
1

Year Published

1971
1971
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 7 publications
1
6
1
Order By: Relevance
“…The highest levels have been detected particularly in immature fruits. Its possible role as a polyphenol oxidase substrate could not be established 34. In our study the arbutin contents were higher than those previously reported in D'Anjou and Bosc pear flesh 5…”
Section: Resultscontrasting
confidence: 91%
“…The highest levels have been detected particularly in immature fruits. Its possible role as a polyphenol oxidase substrate could not be established 34. In our study the arbutin contents were higher than those previously reported in D'Anjou and Bosc pear flesh 5…”
Section: Resultscontrasting
confidence: 91%
“…Such an increase could trigger pear browning, since arbutin has been described as a polyphenol oxidase substrate. 23 In the flesh and peel of apples, the concentration of phenolic compounds (flavan-3-ols and chlorogenic acid) decreased during development at early stages of ripening, 24,25 in agreement with our results, which encompassed a decreasing trend of these compounds after harvest and throughout the whole ripening period.…”
Section: Influence Of Storage Conditions On Phenolic Contentsupporting
confidence: 80%
“…Its possible role as a polyphenol oxidase substrate could not be established. 34 In our study the arbutin contents were higher than those previously reported in D'Anjou and Bosc pear flesh. 5 Regarding total phenolics in the peel, Red D'Anjou had the highest content (200.5 mg kg −1 peel), followed by Bosc and Forelle (166.5 and 164.1 mg 100 g −1 peel respectively).…”
Section: Phenolic Content In Pear Peel and Fleshmentioning
confidence: 99%